Optical frequency combs generated in silica microspheres in the telecommunication C-, U-, and E-bands - Anashkina, Elena A.; Marisova, Maria P.; Salgals, Toms; Alnis, Janis; Lyashuk, Ilya; Leuchs, Gerd; Spolitis, Sandis; Bobrovs, Vjaceslavs; Andrianov, Alexey V. (Photonics, 2021)
Optical frequency combs (OFCs) generated in microresonators with whispering gallery modes are demanded for different applications including telecommunications. Extending operating spectral ranges is an important problem for wavelength-division multiplexing systems based on microresonators. We demonstrate experimentally three spectrally separated OFCs in the C-, U-, and E-bands in silica microspheres which, in principle, can be used for telecommunication applications. For qualitative explanation of the OFC generation in the sidebands, we calculated gain coefficients and gain bandwidths for degenerate four-wave mixing (FWM) processes. We also attained a regime when the pump frequency was in the normal dispersion range and only two OFCs were generated. The first OFC was near the pump frequency and the second Raman-assisted OFC with a soliton-like spectrum was in the U-band. Numerical simulation based on the Lugiato–Lefever equation was performed to support this result and demonstrate that the Raman-assisted OFC may be a soliton.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Four-wave mixing; Optical frequency comb (OFC); Raman OFC; Silica microsphere; Soliton-like spectrum